Dinamika Tenaga Kerja Asing Terhadap Tenaga Kerja Lokal: Implikasi dan Tantangan dalam Investasi Sumber Daya Manusia - Ibrahagi Ramadhano; Gunardi Lie (UNES Law Review, 2023)
The issue of foreign workers is increasingly receiving media and national attention. However, to date research into the nature and consequences of employing foreign workers in Indonesia is still limited. The introduction of significant changes in the recruitment phenomenon ended in a painful and traumatic atmosphere that was almost unacceptable for the local workforce in Indonesia. This research aims to look from an industrial relations perspective which plays an important role in employing foreign workers. The research results will show the employment status of local workers and the rights of local labor unions which are affected by the use of foreign workers. In addition, the research provides a number of recommendations, including the need for further development in reducing the employment of foreign workers and better targeting of vulnerable foreign workers in relation to labor laws.